Enteral nutritional strategy during therapeutic hypothermia: who? when? what? - Simonetta Costa; Irene Del Rizzo; Simona Fattore; Francesca Serrao; Francesca Priolo; Mirta Corsello; Eloisa Tiberi; Milena Tana; Paola Catalano; Giovanni Vento (Frontiers Media S.A., 2024)
BackgroundThere are no guidelines regarding enteral feeding (EF) of infants with hypoxic-ischemic encephalopathy (HIE) during and shortly after therapeutic hypothermia; consequently, clinical practice is, to date, still variable. The objective of this study is to assess whether a minimal EF strategy during therapeutic hypothermia may be associated with a shorter time to full EF of infants with HIE and to identify the clinical variables that independently affect the time to full EF.MethodsA retrospective study, covering the period from 1 January 2015 to 30 June 2022 was performed at the Neonatal Intensive Care Unit of the Fondazione Policlinico Universitario "Agostino Gemelli" IRCCS, Rome, which compared infants with HIE who received minimal EF during therapeutic hypothermia with those who did not.ResultsSeventy-eight infants received minimal EF during therapeutic hypothermia, while 75 did not. Infants who were fed reached full EF significantly faster than those who were not. Moreover, they received parenteral nutrition and maintained central venous lines for a shorter time. A multivariate analysis, taking into account the variable of clinical severity, confirmed that minimal EF is an independent beneficial factor for reaching full EF in a shorter time and mechanical ventilation and seizures are independent factors for a longer time to full EF.ConclusionsMinimal EF during therapeutic hypothermia is associated with a shorter time to full EF in stable infants with HIE. Further prospective studies are needed to better define the enteral nutrition strategy for infants during therapeutic hypothermia, regardless of the severity of clinical conditions.